2017
DOI: 10.7150/thno.17711
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Effects of Ac4ManNAz and Optimization of Metabolic Labeling for Cell Tracking

Abstract: Metabolic labeling techniques are powerful tools for cell labeling, tracking and proteomic analysis. However, at present, the effects of the metabolic labeling agents on cell metabolism and physiology are not known. To address this question, in this study, we analyzed the effects of cells treated with Ac4ManNAz through microarray analysis and analyses of membrane channel activity, individual bio-physiological properties, and glycolytic flux. According to the results, treatment with 50 μM Ac4ManNAz led to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 53 publications
7
21
0
Order By: Relevance
“…As shown in Figure 4 b, no modification of the morphology of the cells was observed even at the highest dose of 200 µM of the chemical reporter, showing that the toxicity of the azidosugar concentration was negligible even at the highest concentrations. Acetic acid release inside cells upon enzymatic deacetylation of Ac 4 GalNAz did not seem to induce cytotoxicity, as was previously reported for Ac 4 ManNAz (>50 μM) [ 23 ]. In order to promote high FRET efficiencies, we chose the highest non-toxic Ac 4 GlcNAz concentration of 200 µM.…”
Section: Resultssupporting
confidence: 79%
“…As shown in Figure 4 b, no modification of the morphology of the cells was observed even at the highest dose of 200 µM of the chemical reporter, showing that the toxicity of the azidosugar concentration was negligible even at the highest concentrations. Acetic acid release inside cells upon enzymatic deacetylation of Ac 4 GalNAz did not seem to induce cytotoxicity, as was previously reported for Ac 4 ManNAz (>50 μM) [ 23 ]. In order to promote high FRET efficiencies, we chose the highest non-toxic Ac 4 GlcNAz concentration of 200 µM.…”
Section: Resultssupporting
confidence: 79%
“…Many hurdles remain to the widespread acceptance of labeling for cell tracking and labeling for stem cell-derived cardiomyocytes because the functional changes of labeling agents in cells are not fully understood. Although these materials have biocompatibility in the cells, many previous studies have shown that the carbocyanine dyes with highly lipophilic nature and nano-materials such as QD specifically led to changes in bio-physiological function, cellular signaling pathways and interference with cell-cell communication ( 4 - 6 , 25 , 26 ). Indeed, carbocyanine dyes showed at high concentrations in cancer cell lines ( 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The transportation of labeling agents into the cells could change the biological responses of cells, such as metabolism, proliferation, and migration ( 4 - 6 ). Labeling agent-rich regions cause changes in the physical properties of the cell surface and thereby determine cellular characteristics, i.e., the cell surface, repulsion between cells, subsequent migration, and the uptake of ion ( 7 - 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is not clear how does this occur, but a similar trend has been observed in literatures. [26, 30, 31]…”
Section: Resultsmentioning
confidence: 99%